OPTIMIZATION OF OUTCOME PROGRAM VOCATIONAL LONG-LIFE EDUCATION “PKBM BINA WARGA KENDAL” THROUGH THE DEVELOPMENT OF ENTREPRENEURIAL-BASED WEBSITE - Kardoyo, Kardoyo; Feriady, Muhammad; Farliana, Nina; Pitaloka, Lola Kurnia (Indonesian Journal of Devotion and Empowerment, 2021)
Vocational Education Package C program implemented by PKBM Bina Warga Kab. Kendal has been proven to have excellent entrepreneurial spirit outcomes. However, there are still major shortcomings in the field of blended learning-based education management. This article describes the picture of the completion of non-formal entrepreneurial learning solutions that are very important to open new jobs. The concept of vocational long-life education is intended as an equality-based education at the level organized by PKBM Bina Warga Kendal. The method of devotion carried out to alleviate the solution is to provide a series of Entrepreneurial Web-based training activities, namely learning websites as well as a web marketing for entrepreneurial training products. The result of the devotion carried out is a new pattern in conducting entrepreneurship and marketing training compared to before the activity was carried out. The new pattern is the existence of digital marketing learning as well as strengthening the character of entrepreneurship through technology. The advice that can be given after the implementation of devotion is the existence of digital marketing training as a strengthening of entrepreneurship in the field of marketing using existing websites and other platforms. Program Paket C Pendidikan Vokasi yang dilaksanakan oleh PKBM Bina Warga Kabupaten Kendal sudah terbukti memiliki outcome jiwa wirausaha yang sangat baik. Akan tetapi masih terdapat kekurangan utamanya dalam bidang pengelolaan pendidikan berbasis Blended learning. Artikel ini menjelaskan gambaran penyelesaian solusi pembelajaran kewirausahaan non formal yang sangat penting dalam rangka membuka lapangan pekerjaan baru. Konsep vocational long-life education dimaksudkan sebagai pendidikan berbasis kesetaraan dalam jenjang yang diselenggarakan oleh PKBM Bina Warga Kendal. Adapun metode pengabdian yang dilakukan untuk mengentaskan solusi tersebut adalah dengan memberikan serangkaian kegiatan pelatihan Entrepreneurial Web based, yaitu website pembelajaran sekaligus di dalamnya adalah web pemasaran untuk produk hasil pelatihan kewirausahaan. Hasil dari pengabdian yang dilakukan adalah adanya pola baru dalam melakukan pelatihan kewirausahaan dan pemasaran dibandingkan sebelum kegiatan dilaksanakan. Pola baru tersebut adalah adanya pembelajaran digital marketing sekaligus penguatan karakter kewirausahaan melalui teknologi. Adapun saran yang bisa diberikan pasca pelaksanaan pengabdian adalah adanya pelatihan digital marketing sebagai penguatan kewirausahaan dalam bidang pemasaran menggunakan Website yang sudah ada maupun platform lainnya.